Encoding and Decoding Black and White Cultural Capitals: Black Middle-Class Experiences. (March 2019) - Meghji, Ali
Drawing upon 23 qualitative interviews, and ethnographic work in London, this article explores how black middle-class individuals in the UK decode forms of middle-class cultural capital. This decoding is two staged. Firstly, black middle-class individuals often decode dominant or 'traditional' middle-class cultural capital as white. This involves a recognition that certain forms of middle-class cultural capital are marked as racially exclusive, and are reproduced and recognised in 'white spaces'. Secondly, black middle-class individuals also decode alternative forms of cultural capital as woven into a greater project of racial uplift. Such alternative forms of cultural capital are defined as 'black cultural capital', and tend to be based around fulfilling a cultural politics of black representation.